Individual Differences in Behavioural Responses to the Financial Threat Posed by the COVID-19 Pandemic - Magdalena Adamus; Matúš Grežo (Masaryk University, Faculty of Economics and Administration, 2021)
Using a representative sample of 400 Slovaks, the study investigated the mediating role of subjective perception of financial threat to the relation between psychological resources and behavioural responses in the adaptation to financial stress posed by the COVID-19. The results showed that greater neuroticism and uncertainty intolerance were positively related to aggravated perception of financial threat. This led to greater willingness to change consumption patterns and use of mostly problem-focused coping strategies. The model remained robust after controlling for chronic financial hardship moderators, including the absence of savings and indebtedness. In contrast, acute financial hardship caused by the deterioration of one's financial situation during the pandemic showed to significantly moderate the relation between one's psychological resources and perceived financial threat.
Keywords: D91; G41; 330; financial threat; neuroticism; uncertainty intolerance; consumption patterns; coping strategies; COVID-19